Enterprise Resource Planning: Analysis and Utilization of Open Source Applications with the EAP Method - Solihin, Hanhan Hanafiah (Jurnal Manajemen Informatika JAMIKA, 2024)
System automation is currently very much needed for the small and medium business industry to large-scale companies. The computerized systems concept is increasingly in demand due to the shift in the industrial era 4.0. Enterprise Resource Planning (ERP) is a multi-module application that puts forward the concept of an integrated computerized system that stores all company data in one easily accessed database. This study discusses open source ERP applications for Micro, Small, and Medium Enterprises by looking at the running business processes that will then adjust to the ERP application module facilitated by the developer. The Enterprise Architecture Planning method acts as an analysis stage and a tool used in business process analysis using the Unified Modeling Language to identify all actors involved and a matrix of relationships between data entities, business processes, and applications. This research provides recommendations modules that can use in open source ERP applications appropriate for the company.